The miR-183/96/182 Cluster Regulates Oxidative Apoptosis and Sensitizes Cells to Chemotherapy in Gliomas - Tang, Hailin; Bian, Yanhui; Tu, Chaofeng; Wang, Zeyou; Yu, Zhibin; Liu, Qing; Xu, Gang; Wu, Minghua; Li, Guiyuan (Current Cancer Drug Targets, 2013)
Many microRNAs reside in clusters in the genome, are generally similar in sequence, are transcribed in the same direction, and usually function synergistically. The miR-183/96/182 cluster is composed of 3 miRNA genes, and increased expression of miR-183, 96 and 182 are implicated in glioma carcinogenesis. Knockdown of individual components or of the entire miR-183/96/182 cluster inhibits the survival of glioma cells by regulating the ROS-induced apoptosis pathway. Furthermore, inhibition of the miR-183/96/182 cluster induced ROS-mediated AKT/survival independent of three target genes FGF9, CPEB1, and FOXO1, and inhibition of the miRNA cluster induced p53/apoptosis signaling, which was dependent on these same genes. In addition, knockdown of the miR-183/96/182 cluster enhanced the anticancer effect of Temozolomide on glioma cells by the ROS-mediated apoptosis pathway. Therefore, the miR- 183/96/182 cluster may be a pleiotropic target for glioma therapy.
Keywords: mitochondrial membrane potential